130 Fever in an intravenous drug user: if it isn't endocarditis then what is it?. (May 2019) - Straw, Sam; Baig, Wazir; Wu, Jianhua; Sandoe, Jonathan
Abstract : Background: Intravenous drug use (IVDU) is a predisposition for the development of infective endocarditis (IE). The incidence amongst people who inject drugs (PWID) is estimated to be 50–100 times greater than the general population. For this reason, PWID with symptoms of infection or bacteraemia are frequently referred to the IE team for assessment. We have previously reported on our experience of managing PWID with IE over more than a decade. Here we present the characteristics, final diagnoses and outcomes in all PWID admitted to hospital with other infections in whom IE was suspected. Methods: Patients aged 18 or over who had taken drugs intravenously within 90 days and referred to the IE team between 01/01/2006 and 31/12/2016 were eligible. Inclusion was dependent on the modified Duke criteria, we required patients to be either Duke criteria negative, or Duke possible and not treated for IE. PWID referred to the IE team who were either Duke definite or Duke possible and treated for IE acted as a comparison group. Patient demographics, microbiology, final diagnoses, survival and causes of death were recorded. Results: There were 112 episodes of other infections in 107 PWID during the study period. 69 (65%) patients were male, and the mean age was 36 ± 8.4 years. During the same period, we assessed and treated 105 episodes of confirmed IE in 92 PWID. There were positive blood cultures in 71 episodes, most commonly Staphylococcus aureus (39), coagulase negative Staphylococcus (3), beta-haemolytic Streptococcus (16), oral Streptococcus (7), Streptococcus angionosis (4), Enterococcus spp. (2), Pseudomonad (1) and other (7). In 10 episodes there was combined infection with two or more microorganisms, and in 41 episodes blood cultures were negative. Where IE was excluded, the final diagnosis was usually an infected deep vein thrombosis (DVT) (41) or skin and soft tissue infection (26). Other infections included osteomyelitis (9), septic arthritis (6), septic pulmonary emboli/lung abscess (5), central line infection (4), pneumonia (4), urinary tract infection (2), pericarditis (2) and in one episode there was a cerebral abscess. Survival following hospitalisation with an episode of infection was 91%, 86.4%, 83.5% and 70% at 1, 3, 5 and 10 years respectively. In univariate analysis, survival was significantly higher in PWID with other infections compared to those treated for IE during the same period (p=0.0002) (figure 1 ). During a median follow-up of 4.8 years there were a total of 26 deaths, with suicide or drug overdose being the cause of death in 9 cases. Conclusion: In approximately half of PWID referred to the IE team the final diagnosis was non-cardiac infection. In those with other infections the alternative diagnosis was usually an infected DVT or skin/soft tissue infection. Survival was favourable in those with other infections compared to those treated for IE. The implication of this finding is that cardiac infection has a negative impact on survival in PWID beyond infection elsewhere. It seems likely that damaged native heart valves, or indwelling prosthetic material poses additional risk of re-infection in the context of ongoing drug use. The continuing high mortality rate in both groups suggests that improving the support offered to PWID might affect outcomes in the longer term. Conflict of Interest: None